2000
DOI: 10.1016/s0092-8674(00)00068-4
|View full text |Cite
|
Sign up to set email alerts
|

Ciboulot Regulates Actin Assembly during Drosophila Brain Metamorphosis

Abstract: A dynamic actin cytoskeleton is essential for the remodeling of cell shape during development, but the specific roles of many actin partners remain unclear. Here we characterize a novel actin binding protein, Ciboulot (Cib), which plays a major role in axonal growth during Drosophila brain metamorphosis. Loss of Cib function leads to axonal growth defects in the central brain, while overexpression of the gene during development leads to overgrown projections. The Cib protein displays strong sequence similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
109
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 55 publications
11
109
2
Order By: Relevance
“…As outlined in detail in Materials and Methods, this SPR analysis demonstrates that at least three actin monomers can simultaneously interact with one tetraThymosin␤ molecule. This is clearly in contrast with conclusions made for the homologous protein ciboulot where a 1:1 stoichiometry is proposed (Boquet et al, 2000;Hertzog et al, 2002Hertzog et al, , 2004. The steepness of the slopes of the binding curves suggests that on and off rates are fast.…”
Section: Tetrathymosin␤ Binds Multiple Actin Monomers and Has Both Secontrasting
confidence: 80%
See 3 more Smart Citations
“…As outlined in detail in Materials and Methods, this SPR analysis demonstrates that at least three actin monomers can simultaneously interact with one tetraThymosin␤ molecule. This is clearly in contrast with conclusions made for the homologous protein ciboulot where a 1:1 stoichiometry is proposed (Boquet et al, 2000;Hertzog et al, 2002Hertzog et al, , 2004. The steepness of the slopes of the binding curves suggests that on and off rates are fast.…”
Section: Tetrathymosin␤ Binds Multiple Actin Monomers and Has Both Secontrasting
confidence: 80%
“…The actin-binding determinants of this module are clearly delineated: a hexapeptide motif ( 17 LKKTET 22 in thymosin␤4) and a hydrophobic cluster in a preceding ␣-helix (Vancompernolle et al, 1992;Van Troys et al, 1996b;Rossenu et al, 1997;Simenel et al, 2000;Rossenu et al, 2003;Domanski et al, 2004). Given their repeated structures, tetraThymosin␤, Drosophila ciboulot, and the amoebal protein actobindin (harboring four, three, and two repeats, respectively; Lambooy and Korn, 1986;Van Troys et al, 1999;Boquet et al, 2000) form a novel subset of ␤-thymosins. Both ciboulot and actobindin have been demonstrated to display a similar promotive effect on filament growth as is observed Article published online ahead of print.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although WH2-domains from different proteins may share only 15% sequence identity, their common feature is their ability to bind to the barbed-end face of actin. Meanwhile WH2-domains were discovered in about 38 other proteins [see also Hertzog et al, 2004], mainly actin binding proteins, which regulate the organization of the actin cytoskeleton like actobindin possessing two b-thymosin-repeats each containing a WH2-domain [Vancompernolle et al, 1991], ciboulot-a protein with three b-thymosin-repeats found in Drosophila [Boquet et al, 2000], and the nucleating protein Spire, which was first discovered in Drosophila containing four WH2-domains in series [Quinlan et al, 2005]. In contrast to b-thymosins, most of these proteins (such as actobindin, ciboulot, and Spire) support actin polymerization.…”
Section: Structure Of the Actin:thymosin B4 Complexmentioning
confidence: 99%